Osadnictwo pradziejowe wyspy czerskiej - Grabarczyk, Tadeusz (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
Primaeval settlement in the area of Czersk in the northern part of Tuchola Forests began in mesolythic period. Traces of neolitic cultures are scare as for example the biggest of them the culture of funnel-shaped caps. Also Lusatian culture is very sporadic and only Pomeranian culture is rich represented especially by box graves. Directly after the Pomeranian culture the Wielbark culture appeared the classical representative of which is the cemetery with stone circles in Odry. This is the last of the primaeval cultures of this region. It is stressed that the settlement and the type of husbandry were very much dependent on the difficult ecological conditions specially in this region.